STUDI PENGARUH ADITIF KAPUR TERHADAP PENGEMBANGAN, KUAT TEKAN BEBAS DAN KUAT GESER TANAH EKSPANSIF DI CIKAMPEK (JAWA BARAT) - Pasya Reihan Beyruni, Abdi
The objective of this thesis was to study experimentally the affect of lime for stabilizing expansive soil. The study included chemical and mineral behaviour, Atterberg Limits, Grain Size Distributions, Free Swell and Swelling Pressures, Unconfined Compressive Strength and Saturated Triaxial Unconsolidated Undrained Shear Strength, of both natural and stabilized soils. The expansive soil sample was taken from Cikampek, West Java. The Liquid Limit (LL) and the plasticity Index (PI) of this sample was 98.5% and 70.58% respectively. The stabilized soil samples were prepared by first compacting the natural soil to its maximum dry density using standard proctor test. Then lime was added to this compacted soil. The content of lime used in this studey varied from 3% to 15% by weight. The stabilized specimens were cured first before conducting the tests. The curing time varied from 0 to 7 days. The results of this study show that adding lime to the natural expansive soil reduced the LL, PI, free swell and sweling pressure of the soil, and that adding lime to the natural expansive soil increased the shear strength of the soil. For example: adding 3 % of lime with zero curing time reduced the free swell and swelling pressure of the natural soil by 28% and 25%, respectively, while the shear strength increased by 7.7%.